2018
DOI: 10.1007/s00221-018-5359-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-stimulus theta power is correlated with variation of motor evoked potential latency: a single-pulse TMS study

Abstract: There has been a growing interest in the role of pre-stimulus oscillations on cortical excitability in visual and motor systems. Prior studies focused on the relationship between pre-stimulus neuronal activity and TMS-evoked motor evoked potentials (MEPs) have reported heterogeneous results. We aimed to assess the role of pre-stimulus neural activity on the latency of MEPs, which might enhance our understanding of the variability of MEP signals, and potentially provide information on the role played by cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…Interestingly, the consistency of our spectral power results between different modalities and paradigms differs from previous findings, which showed task-specific relationships between pre-stimulus spectral power and poststimulus ERP components 29 , 79 , 81 . This may, in part, be due to the fact that we investigated the same neurophysiological variables during the transition from prestimulus to post-stimulus period; alternatively, they may be due to the use of time-domain signals to operationalize stimulus response, as we likewise observed task-specific spontaneous-evoked correlations in our ERP data.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the consistency of our spectral power results between different modalities and paradigms differs from previous findings, which showed task-specific relationships between pre-stimulus spectral power and poststimulus ERP components 29 , 79 , 81 . This may, in part, be due to the fact that we investigated the same neurophysiological variables during the transition from prestimulus to post-stimulus period; alternatively, they may be due to the use of time-domain signals to operationalize stimulus response, as we likewise observed task-specific spontaneous-evoked correlations in our ERP data.…”
Section: Discussioncontrasting
confidence: 99%
“…By probing directly corticospinal excitability, Transcranial Magnetic Stimulation (TMS) studies provide more compelling evidence that neuronal oscillations actually entail cyclic modulations of the motor system excitability. Indeed, motor evoked potentials (MEPs) are modulated not only by the amplitude (İşcan et al, 2018;Keil et al, 2014;Mäki and Ilmoniemi, 2010;Schulz et al, 2014) but also by the pre-TMS phase of ongoing oscillations at both peripheral (i.e., muscle activity; Keil et al, 2014, van Elswijk et al, 2010 and cortical level (Berger et al, 2014;Keil et al, 2014;Khademi et al, 2018). The use of neuromodulation techniques, such as transcranial Alternating Current Stimulation (tACS), in combination with TMS, have further shown that entrained, in addition to ongoing, beta-band oscillations affect MEPs size in a phase-dependent manner (Guerra et al, 2016;Nakazono et al, 2016;Raco et al, 2016;Schilberg et al, 2018).…”
Section: Action-perception Coupling: Possible Mechanisms and Functionmentioning
confidence: 99%
“…In these applications, an array of signal processing methods have been applied to EEG signals over the past two decades many of which were summarized by Bashashati et al [13]. Using the processing methods, an array of features is usually extracted from the EEG signals [14][15][16][17][18][19][20]. The features are then used for various tasks such as statistical analysis or machine learning based methods [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Using the processing methods, an array of features is usually extracted from the EEG signals [14][15][16][17][18][19][20]. The features are then used for various tasks such as statistical analysis or machine learning based methods [14][15][16][17][18][19][20][21]. The EEG signal processing methods, in themselves, have a number of selection parameters, which have been found to be selected inconsistently across different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation